A DOENÇA E O PODER PÚBLICO OU O PODER DAS DOENÇAS: ELEMENTOS PARA UMA ANÁLISE EM TORNO DO ESTADO NO COMBATE À TUBERCULOSE (Revista de História Regional, 2007)
This paper focuses the city of Rio de Janeiro during the end of the 19th Century and the beginning of the 20th Century. We analyse the problem of tuberculosis in relation to the State action which, during the first two decades of the 20th Century, was reduced to sanitary laws, subventions to philantropy and plans which led to the State to assume, in 1920, the tuberculosis matter creatind the Tuberculosis Prophylaxis Inspectorate.